KONTRAK MUSAMMA JUSTIFIKASINYA DALAM TRANSAKSI KEWANGAN ISLAM SEMASA: Nominate Contracts: Its Justifications in Contemporary Islamic Financial Transactions - Che Abdullah, Ahmad Sufyan (Jurnal Syariah, 2011)
In dealing with modern Islamic financial engineering, Shariah provides us with considerable flexibility to invent new contracts, as long as we do not contravene the basic principles of Islamic law. In addition, we found that Shariah scholars in their classical works on Islamic law paid great attention to the nominate contracts; the contracts that historically have specific names with specific features. Through our research on the classical works of Islamic law, all these nominate contracts play a vital role as a basis for any new invention in financial contracts. This research, however, found that the specific names, such as syarikah, ijarah, wakalah, etc., are meaningless in Islamic law except to differentiate between the characteristics of each contract. Hence, the justification to refer new contracts to classical nominate contracts is to ensure that the legal impact of the new contracts does not lead to any prohibited contract or any wrong combination of two or more contracts that contradict each other, as well as to verify that the contracts will not oppose the general objectives (maqasid 'ammah) of Shariah.